Papua new Guinea : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2006)
This Selected Issues paper on Papua New Guinea reports that although economic cycles have generally paralleled the many mineral sector booms and busts, the downward trend in growth rates may reflect other factors. Papua New Guinea's economy is dominated by a large labor-intensive agricultural sector and a capital-intensive oil and minerals sector. The formal sector consists of enclave extractive industries, cash crop production, and a small, import-substituting manufacturing sector. The importance of the agriculture sector is about the same as at independence, reflecting structural impediments that have deterred more rapid growth.